Penerapan Menuntut Ilmu Pengetahuan Perspektif Syaikh Az-Zarnuji Dalam Kitab Ta’lim Al-Muta’allim - Nur Khalifah, Muhammad Saleh, Ahmad Fuadi (Khazanah : Journal of Islamic Studies, 2023)
Shaykh Az-Zarnuji is a Muslim scholar or scholar who has thoughts in studying knowledge. The book in particular which is quite well known and is a reference among Muslims is the book of Ta'lim Muta'allim. Shaykh Az-Zarnuji's thoughts in the book of muta'allim ta'lim contain adab-adab in education. The objectives of this research were: To find out the purpose and application of studying knowledge from the perspective of Sheikh Az Zarnuji in the book of Ta'lim Muta'allim. This type of research is library research. The research object is explored through a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). This study uses a philosophical approach, data collection techniques, namely documentation with data analysis techniques, namely data reduction, data display, and drawing conclusions. The results of this study show that there are 3 goals for studying, namely individual goals; Social goals and professional goals. The goals are individual, namely eliminating ignorance from oneself, educating the mind, being grateful for the blessings of the mind and body health. The goals are social, namely eliminating stupidity from members of the community (educating the community), reviving Islamic religious values. Meanwhile, the professional goal is to master knowledge which has implications for the achievement of the position that has been achieved is for the benefit of the people as a whole. These three goals must be based on the main goal of getting the blessing of Allah SWT. Then in applying the demand for knowledge there are several things that must be considered, namely the intention when studying; choose knowledge, teachers, and friends; respect science and scientists; have seriousness, perseverance and lofty ideals; choose the correct method of seeking knowledge; trust; and has the nature of wara'.